Role of tissue C4d in differentiation between acute rejection and HCV recurrence after living donor liver transplantation - Eldin Hamza Khalil, Zeinab Salah; Dandarawy Hassan, Waleed Gad (International Journal of Advances in Medicine, 2020)
Background: Liver biopsy represents the gold standard for diagnosis of acute rejection and HCV recurrence after liver transplantation; never the less discrimination can be difficult due to similar display of alterations in liver specimen. Therefore, a specific marker expressed only in rejection but not in HCV recurrence would be a great asset to differentiate between both conditions. The aim of this study was to assess the role of tissue C4d complement fragments in liver biopsy as a marker for differentiating between acute rejection and HCV recurrence in recipients post LDLT. Methods: A case control study on 25 recipients after liver transplantation with the suspicion of either acute rejection or HCV disease recurrence, patients were classified according to pathological finding into two groups, Group 1: patients with acute rejection (n=13), Group 2: patients with HCV recurrence (n=12), The C4d was evaluated by immunohistochemical staining of the formalin-fixed, paraffin-embedded tissue in different liver compartments. Results: C4D staining of all the studied tissue compartments (Sinusoids, portal vein endothelium, hepatic vein endothelium, arterial internal elastic lining, portal stroma, bile ducts) had high specificity (100%) and positive predictive value (100%) in diagnosis of rejection cases except portal vein endothelium. (Specificity 91.7%, positive predictive value 88.9%). Conclusions: Tissue C4d staining was almost present in rejection cases only; further studies on larger cohort are required to stand on standard diagnostic criteria for C4d to be included in diagnosis of acute rejection after liver transplantation as its role in other organ transplantation.